Pengaruh Kualitas Pelayanan dan Komunikasi Interpersonal terhadap Kinerja Karyawan pada Kantor Marvel Flooring: The Influence of Service Quality and Interpersonal Communication on Employee Performance at Marvel Flooring Offices - Fauza Kamila; Susanti Susantu (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the effect of service quality and interpersonal communication on employee performance at Marvel Flooring Office. This research employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to employees of Marvel Flooring Office as respondents. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination analysis, t-test, and F-test with the assistance of IBM SPSS Statistics software. The findings indicate that service quality has a positive and significant effect on employee performance. Interpersonal communication also has a positive and significant effect on employee performance and is the most dominant factor influencing employee performance. Furthermore, service quality and interpersonal communication simultaneously have a positive and significant effect on employee performance. The coefficient of determination shows that both independent variables explain a substantial proportion of the variation in employee performance. This study concludes that improving service quality and interpersonal communication is essential for enhancing employee performance. Therefore, the company should maintain high service quality and foster effective interpersonal communication to support better employee performance.